Detection of meat-borne trimethylamine based on nanoporous colorimetric sensor arrays. (15th April 2016) - Xiao-wei, Huang; Zhi-hua, Li; Xiao-bo, Zou; Ji-yong, Shi; Han-ping, Mao; Jie-wen, Zhao; Li-min, Hao; Holmes, Mel
Highlights: Fabricating a nanoporous colorimetric sensor array based on TiO2 . The nanoporous structure can improve the stability and homogeneity of colorimetric sensor. The sensor was used to detect 60 ppb of TMA. The nanoporous colorimetric sensor was used to detect TMA in Yao -meat. The color changes of sensors were correlated with conventional method for predication TMA by PLS. Abstract: Trimethylamine (TMA) is a key measurement indicator for meat spoilage. In order to develop simple, cheap, and sensitive sensors for TMA detection, a nanoporous colorimetric sensor array (NCSA) was developed. A sol–gel method has been used to obtain TiO2 nanoporous film as substrate material to improve the sensitivity and stability of the CSA. The sensor enabled the visual detection of TMA gas from the permissible exposure limits (PEL) 10 ppm to 60 ppb concentrations with significant response. Principal component analysis (PCA) was used to characterize the functional relationship between the color difference data and TMA concentrations. Furthermore, the NCSA was used to predict the presence of TMA in Yao -meat. A partial least square (PLS) prediction model was obtained with the correlation coefficients of 0.896 and 0.837 in calibration and prediction sets, respectively. This research suggested that the NCSA offers a useful technology for quality evaluation of TMA in meat.